Análise de sobrevida do enxerto de pacientes transplantados renais, em esquema de manutenção imunossupressora no SUS, Brasil: 2000 a 2010 - Rosângela Maria Gomes (2015)
Introduction: Chronic kidney disease (CKD) is characterized by progressive and irreversible deterioration of kidney function. Its main causes are hypertension and diabetes mellitus. The survival of patients with end-stage renal disease is subject to the use of renal replacement therapy (RRT). Among the options, renal transplantation is the RRT of choice for patients who do not have contraindications to do so, as it offers improved survival and quality of life, and is more cost-effective than dialysis. In Brazil, the Unified Health System (SUS) is responsible for almost all renal transplants performed in the country, and it ensures access to immunosuppressive medicines. The Therapeutic Guidelines and Clinical Protocols of the Specialized Component of Pharmaceutical Assistance recommend the use of therapeutic regimens with cyclosporine or tacrolimus associated with a corticosteroid and an anti-proliferative agent. Regarding the provision of immunosuppressants by SUS since 1982 the results of its long-term use remain unknown. Objectives: Analyze 10 years graft survival of renal transplant patients focusing on maintenance therapy with cyclosporine or tacrolimus. Methods: This study consisted of a nationwide historic cohort developed through deterministic-probabilistic linkage of SUS administrative data-bases: Hospital Information System (SIH/SUS); Subsystem for High Complexity Procedures (SIA/SUS) and the Mortality Information System (SIM). 13.489 patients transplanted from 01/01/2000 to 12/31/2009 that used immunosuppressive regimens with cyclosporine or tacrolimus were included and observed from 01/01/2000 to 12/31/2010. We evaluated treatment failure (death or graft survival) through the overall survival curves by immunosuppressive regimen (cyclosporine and tacrolimus), sex and age of the recipient, primary diagnosis of the cause of CKD, donor type, and time of dialysis prior to transplantation. For the survival curves we used the Kaplan-Meier method and to compare them we used Log Rank test. For univariate and multivariate analysis of risk factors associated with treatment failure we used the Cox regression method. Results: In 10 years the overall graft survival was 72.2%. Treatment regimen with cyclosporine showed survival of 73.2% whereas for patients who used tacrolimus survival was 69.6%. Most patients were male with a mean age of 41 years. The most common primary diagnosis of chronic kidney disease (CKD) was glomerulonephritis/interstitial nephritis/pyelonephritis. Increased risk for graft loss was associated with the use of tacrolimus (HR = 1.162, 95% CI 1.051 to 1.285), graft from deceased donor (1.630; 1.468 to 1.612), being male (1.151; 1.043 to 1.271), patient age (1.012; 1.008 to 1.016), the previous median on dialysis >47 months (1.337; 1.205 to 1.485) and the diagnosis of diabetes mellitus as the primary cause of CKD (1.361; 1.119 to 1.657). Conclusion: Graft survival of transplant patients taking cyclosporine or tacrolimus in SUS at 10 years was 72.2%. Male patients, diabetes mellitus as a cause of CKD, deceased donor graft, and the additional age time and dialysis time were associated with poor survival. In addition, patients using immunosuppressive regimens containing tacrolimus had worse graft survival compared to patients who received cyclosporine. The results were obtained through observational study with more than 13,000 patients and, therefore, with great potential for generalization.